The Character of Philosophy in the Improvement of Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is about the emergence of linguistics, in the process the philosophical views of the philosophers are stated. Of Greek scholars in linguistics views are illuminated. Aspects of the influence of philosophy on linguistics are in the process the importance of other disciplines is highlighted. As a science of general linguistics the formation process is reflected.